ANALISIS PENGARUH FASILITAS DAN AKSESIBILITAS TERHADAP MINAT KUNJUNGAN WISATAWAN PADA DESTINASI GEOPARK SILOKEK SIJUNJUNG - Maulana Muhammad Akbar; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2025)
This research was motivated by the fact that in field observations the author found problems including the accumulation of visitors at the Silokek Geopark, facilities that were not well maintained and not cleaned thoroughly (facilities at the Silikek Geopark were not maintained). Not only that, the information boards were not updated and the roads damaged, accessibility is not well maintained. This research aims to find out and identify how much influence facilities and accessibility have on tourist interest in visiting the Silokek Sijunjung Geopark Destination. This type of research uses a quantitative approach. The results of this research show that: (1) partially the facility variable t_count value is 3.603 and is significant 0.001. So a comparison is obtained with 3.603 > 1.986 and a significant 0.001 < 0.05. Thus, it can be interpreted as having a positive and significant effect on tourist interest in the Silokek geopark tourist destination, and the accessibility variable t_count value is 3.694 and is significant 0.000. So we get a comparison with 3,694 > 1.986. and significant 0.00 < 0.05. Thus, it can be interpreted as having a positive and significant influence on tourist interest in visiting the Silokek Geopark tourist destination. (2) simultaneously for the Facilities and Accessibility variables, the value of F_count > F_table is 19.284 > 3.09 with a significance of 0.001 <0.05. So the results of the F test show that it is positive and significant regarding tourist interest in visiting the Silokek Geopark tourist destination.